2015
DOI: 10.4236/jep.2015.63022
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment of a Tropical Mexican Lake Using Multivariate Statistical Techniques

Abstract: Water quality of Mexican tropical lake Chapala was assessed through multivariate statistical techniques, cluster analysis (CA) and principal component analysis (PCA) at ten different monitoring sites for ten physicochemical variables and six metals. This study evaluated and interpreted complex water quality data sets and apportioned of pollution sources to get better information about water quality. From descriptive statistics results, the highest concentrations of metals occurred during the dry season, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
2
15
0
3
Order By: Relevance
“…The results of the research on the quality parameters of the solar lake were analyzed using selected chemometric procedures and in particular the cluster analysis (CA), Spearman coefficients were calculated between successive water quality indices and the factor analysis (FA). The CA method was used to detect and visualize the similarities and differences between the variability of individual water quality indices, examining the nature of variations for different sampling sites (station numbers) and individual sampling dates The Ward method was used to determine the distance between the clusters -equal squares of the Euclidean distance (Badillo-Camacho et al, 2015;Li et al 2015;Kari et al, 2009;Mustapha et al, 2013;Miller et al, 2016;Najar et al, 2012). The calculation of Spearman correlation coefficients was to determine the relationship between the water quality indexes so as to distinguish independent indices that characterize water quality changes during the research period.…”
Section: Chemometric Proceduresmentioning
confidence: 99%
“…The results of the research on the quality parameters of the solar lake were analyzed using selected chemometric procedures and in particular the cluster analysis (CA), Spearman coefficients were calculated between successive water quality indices and the factor analysis (FA). The CA method was used to detect and visualize the similarities and differences between the variability of individual water quality indices, examining the nature of variations for different sampling sites (station numbers) and individual sampling dates The Ward method was used to determine the distance between the clusters -equal squares of the Euclidean distance (Badillo-Camacho et al, 2015;Li et al 2015;Kari et al, 2009;Mustapha et al, 2013;Miller et al, 2016;Najar et al, 2012). The calculation of Spearman correlation coefficients was to determine the relationship between the water quality indexes so as to distinguish independent indices that characterize water quality changes during the research period.…”
Section: Chemometric Proceduresmentioning
confidence: 99%
“…The presence of potentially toxic substances such as heavy metals and other substances in this water body has prompted concern since large quantities of wastes from municipal, industrial, and agricultural activities from the entire Lerma-Chapala basin flow largely untreated into the lake through the Lerma River (the main tributary to the lake, see Figure 1) (Hansen et al, 1995). Despite the importance this lake has as water supply for human consumption (Badillo-Camacho et al, 2015), only a few studies have being reported concerning the status of the presence of heavy metals and their risk to the water column. Trujillo-Cardenas et al (2010), were the first ones who reported the presence of some metals (lead and chromium) in the exchangeable and carbonate fractions of sediments of lake Chapala.…”
Section: Introductionmentioning
confidence: 99%
“…Camacho et al (2015), analisando as correlações entre as variáveis de qualidade da água de um Lago Tropical na Chapala Mexica, conseguiu explicar 81,8% da variância total por meio de seis fatores.Dessa forma retirara-se dos quatro primeiros fatores os escores fatoriais de cada variável, sendo que os que apresentaram o maior peso em cada fator foram utilizados como representante de cada variável conforme destacado na Tabela 4.…”
unclassified